Effect of Rocker Arm Variation on the Perfonmance of a Single Cylinder Petrol Engine - Winoko, Yuniarto Agus; Setiawan, Angga (Institut Teknologi Sepuluh Nopember, 2024)
The rocker arm functioned as a link between the camshaft and the valve which was responsible for regulating the rise and fall of the valve. Based on how it worked, the roller rocker arm with a conventional rocker arm were the same. However, a significant difference was seen in the roller placed at one end that made direct contact with the camshaft. The use of a conventional rocker arm produced considerable friction, so researchers replaced it with a roller rocker arm. The purpose of this study was to improve the performance of a single cylinder petrol engine using a roller rocker arm that had diameter sizes of 15 mm and 17 mm against the standard. The performance testing method used the variable open throttle to obtain data. Furthermore, the data was presented in graphical form and analyzed using anova. The independent variables were roller rocker arm whose diameter were 15 mm and 17 mm, conventional rocker arm and round 3000, 3500, 4000, 4500, 5000, 5500, 6000, 6500, 7000 rpm. The dependent variables were power, torque and specific fuel consumption. The control variables were engine 100 cc and 92 octane fuel. The largest power result at 6500 rpm was 6.25 Hp using a conventional rocker arm. The largest torque at 3500 rpm was 7.23 Nm using a 15 mm roller rocker arm. The smallest specific fuel consumption was 0.1546 kg/Hpxh at 5000 rpm using a 15 mm roller rocker arm.